2016
DOI: 10.1177/0954408916666303
|View full text |Cite
|
Sign up to set email alerts
|

Numerical performance and safety analyses of a retainer-type ball valve for use in a high-pressure district heating pipeline

Abstract: The performance and safety of a retainer-type ball valve have been evaluated for use in a high-pressure pipeline to a district heating plant. The retainer-type ball valve is a developed valve improving the defects of the leaks that may occur in the general valves such as the floating ball valve or trunnion ball valve. To verify the valve design, a numerical analysis of the design has been applied to investigate safety factors and to determine the flow coefficients for the DN300 and DN400 standard sizes. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Extensive CFD studies of valve flows have been conducted in support of understanding and improving designs. Some examples of such CFD studies can be found in [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Similar to experimental measurements, there are uncertainties/errors in all of the industrially practical CFD methods.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive CFD studies of valve flows have been conducted in support of understanding and improving designs. Some examples of such CFD studies can be found in [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Similar to experimental measurements, there are uncertainties/errors in all of the industrially practical CFD methods.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al 20 conducted a CFD analysis of a wedge-type, double-disc, parallel gate valve and investigated the influence of different working conditions on the gate valve flow rate and loss coefficient. Yang et al 21 used CFD and finite element method (FEM) analyses to study flow characteristics and safety performance of a retainer-type ball valve. Kim et al 22 experimentally investigate the flow characteristics of single, double, and triple eccentric butterfly valves and concentric inclined disc butterfly valves.…”
Section: Introductionmentioning
confidence: 99%